Waterbird Checklist, Threats, and Opportunities for Wetlands Ecosystems in Sukamara Regency, Central Kalimantan - Agusti Randi; Barakalla Robyn; Adhy Maruli; Oby Andrean; Rodianto Rodianto; Ahmad Muammar Kadafi (Pandawa Institute, 2026)
Tropical wetlands are among the most important yet increasingly threatened ecosystems in Southeast Asia, providing critical habitat for biodiversity and essential ecosystem services for local communities. However, information on waterbird assemblages in many peatland landscapes of Borneo remains limited, constraining effective conservation planning. This study presents a preliminary assessment of waterbird diversity, associated threats, and landscape management opportunities in the Bakung River wetlands landscape, Sukamara Regency, Central Kalimantan, Indonesia. Field observations recorded 28 waterbird species belonging to 10 families, including 17 migratory species and several taxa of national and global conservation concern. The findings indicate that the seasonal hydrological dynamics of the Bakung River create an extensive mosaic of open swamp habitats that function as important feeding, resting, and refuge areas for resident and migratory waterbirds. Despite its ecological significance, the landscape is exposed to multiple anthropogenic pressures, particularly recurrent peat fires, canal-driven hydrological disturbance, and destructive fishing practices that may reduce habitat quality and ecosystem resilience. Based on these results, we highlight the need for an integrated landscape approach that combines habitat protection, peatland and hydrological restoration, regulation of unsustainable resource use, and long-term biodiversity monitoring. In addition, innovative sustainable financing mechanisms, including ecotourism and other schemes related to environmental services may provide complementary pathways to support conservation implementation while sustaining local livelihoods. This study underscores the strategic importance of the Bakung River landscape as a wetland refuge for waterbirds in Borneo and provides an initial scientific basis for future ecological research and ecosystem-based management in the region.